Obat Herbal dari Akar Manis (Glycyrrhiza glabra L.) untuk Pencegahan dan Pengobatan Infeksi Virus H1N1, H5N1 dan COVID-19: Systematic Review - Sulutaniyah Sulutaniyah; Endang Darmawan (Jurnal Surya Medika (JSM), 2022)
Herbs have been used as a form of traditional medicine since ancient times. Licorice is one of the herbs that has long been used as medicine. This plant contains different plant compounds, such as glycyrrhizin, 18β‐glycyrrhetinic acid, glabrins A and B, and isoflavones, showing various pharmacological activities. Pharmacological experiments have shown that different extracts and pure compounds of this species exhibit broad biological properties, including antibacterial, anti-inflammatory, antiviral, antioxidant, and antidiabetic activities. This systematic review aims to determine the effectiveness of herbal medicine from licorice (Glycyrrhiza glabra L.) to prevent and treat H1N1, H5N1, and COVID-19 virus infections from various previous research results. This research is a systematic review using the PRISMA method. A total of 8 articles that met the inclusion and exclusion criteria were continued for analysis. A total of 8 articles discuss the effectiveness of licorice on the H1N1, H5N1, and COVID-19 viruses. The articles used include articles published in national journals and international journals. The results showed that 1) Licorice root is effectively used for the prevention and treatment of H1N1, H5N1, and COVID-19 virus infections, 2) Glycyrrhizic acid (GA) is the main compound for the development of potential anti-influenza virus agents. Overall, it can be concluded that licorice and some of its derivatives have the potential as anti-influenza agents for H1N1, H5N1, and COVID-19.